Performance assessment of six public health programs in Katsina State, Nigeria - Laurent Cleenewerck; Devender Bhalla; Kabiru Abubakar Gulma (Intelektual Pustaka Media Utama, 2019)
This research aimed to evaluate the performance of six ongoing public health programs through core performance indicators in Katsina State, Nigeria. The healthcare delivery in Africa is mostly program-based. This requires that such programs need to be evaluated which may in turn help to identify any existing gaps towards the improvement of patients' access and coverage to their given service. We identified all active health facilities where our programs on malaria, Routine Immunization (RI), Family Planning (FP), Tuberculosis and Leprosy (TBL), HIV/AIDS, and Free Medicare (FMC) were being carried out. After that, a representative sample was derived to obtain data regarding five key performance indicators by using a Logistics Indicators Assessment Tool. Of 1,718 facilities, a total of 983 (57.22%) were visited, In other words, by assuming a normal distribution; each facility expectedly covers only 3,371 individuals. All programs provided different and diverse results on each indicator; however, the most obvious challenge was in the stock-out and demand vs. receipt of required medications. These are particularly for malaria, FMC, FP, and HIV. For instance, the stock-out lasted 222 days for malaria and 135 days for FP. Despite this, none of the programs had a lower than gold-standard near-term availability of required products. Program-based healthcare delivery is inadequate and ineffective unless the local system gets simultaneously developed. If required medications are not becoming available, optimal access, coverage, and benefits cannot be expected to be obtained. Clearly, Nigeria experiences a push system of meeting term supplies. Nigeria needs to strengthen its pharmaceutical system.